Methods of Recovering Punctuation Mark in the Text in Speech Recognition System and its Specific Aspects (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides general information about the methods of restoring punctuation marks in the text and its specific aspects in the speech recognition system, and their features are revealed. The issue of punctuation recovery has been analyzed by NLP, a common method for Automatic Speech Recognition (ASR) systems.